THE PRINCIPALS’ TRANSFORMATIONAL LEADERSHIP PRACTICES AND TEACHERS’ MOTIVATION IN SELECTED ISLAMIC PRIVATE SCHOOLS IN SONGKHLA, SOUTHERN THAILAND - Wanlabeh, Natyada; Othman, Azam (International Business Education Journal, 2013)
This study analyses the relationship between principals’ transformational leadership practices and teachers’ motivation in context of Islamic private schools in Songkhla, a southern province of Thailand. Based on survey, the statistical data indicate that teachers’ motivation is significantly related to principals’ transformational leadership practices as perceived by teachers. The study found that although teachers perceive that their principals exhibited transformational leadership more frequently than transactional leadership, the principles are viewed to display more idealized influence and inspirational motivation rather than individual consideration and intellectual stimulation practices. To strengthen the teachers’ motivation in schools, they should exhibit the individual consideration and intellectual stimulation practices more frequently.